Predicting Children's Reading and Mathematics Achievement from Early Quantitative Knowledge and Domain-General Cognitive Abilities - Chu, Felicia W.; vanMarle, Kristy; Geary, David C. (Frontiers in Psychology, 2016)
At the beginning of preschool, we assessed a broad range of quantitative abilities for 100 (43 boys) children, as well as their preliteracy knowledge, intelligence, executive functions, and parental educational background. Mathematics achievement was assessed at the end of each of two years of preschool and at the end of kindergarten, and word reading achievement was also assessed at the end of kindergarten. We identified the core quantitative competencies, such as children’s understanding of the cardinal value of number words, that predict later achievement, the domain-general abilities that predicted growth in these competencies across two years of preschool, and the domain-general and domain-specific abilities that predicted mathematics achievement growth across the preschool years. We also identified similarities in the early domain-general abilities and differences in the domain-specific knowledge that predict mathematics and word reading achievement at the end of kindergarten.